Materials for Electrodes of Li-Ion Batteries: Issues Related to Stress Development. Issue 3 (4th May 2017) - Banerjee, Joyita; Dutta, Kingshuk
ABSTRACT: Presently, rechargeable Li-ion batteries, possessing highest energy densities among all batte-ries, are used in a major fraction of all portable electronic devices. However, for bestowing the Li-ion batteries suitable for such advanced applications, further improvements in the energy densities (Li-capacities) and in the cycle life are essential. In a broader sense, this can be achieved by replacing the presently used electrode materials by materials possessing higher Li-capacities and minimization of the degradation of such materials with electrochemical cycling. It has been realized that the major reason for degradation in battery performance in terms of capacity with cycling is the disintegration/fragmentation of the active electrode materials due to stresses generated during Li-intercalation/de-intercalation in every cycle. Such stresses arise from the reversible volume changes of the active electrode materials during Li-insertion and removal. In quest of higher energy densities, replacement of the presently used graphitic carbon by potentially higher capacity metallic anode materials (like Si, Sn, and Al) is likely to further accrue this stress related disintegration due to ∼30 times higher volume changes experienced by such materials. It has also been recently realized that passivating layer formed on the surface of the electrodes also contributes toward the stress development. After briefly introducing the mechanistic aspects of Li-ion batteries, this article focuses on the reasons and consequences associated with stress developments in different electrode materials, highlighting the various strategies, in terms of designing new electrode com-positions or reducing the microstructural scale, that are being presently adopted to address the stress-related issues. Considering that experimental determination of such stresses is essential toward further progress in Li-ion battery research, this article introduces a recently reported technique developed for real-time measurement of such stresses. It finally concludes by raising some critical issues that need to be resolved through further research in this area.